Evaluation of pathological manifestations in public works and their relationship with repair costs: a case study - Tavares, Thayná Cavalcante; Silva Neto, Dimas de Castro e (Brazilian Journal of Production Engineering, 2024)
The construction sector is crucial to the Brazilian economy, even during periods of crisis, given its significant contribution to the Gross Domestic Product and the stimulation of related sectors' growth. However, the premature deterioration of buildings, often resulting from construction failures or pathological issues, challenges the quality and durability of constructions. This study aims to quantify the impact of pathological manifestations on the repair budgets of three public buildings in Juazeiro do Norte/CE – UBS Vila Três Marias, UBS Socorro, and UBS Betolândia –, highlighting the financial consequences of interrupted works. The methodology includes data collection through technical inspections and photographic documentation, classification of pathological manifestations, recommendation of corrective measures, and cost analysis to quantify the financial impact of deteriorations. The results reveal that halted projects not only delay the delivery of essential infrastructure but also incur additional costs, indicating gaps in project management and contingency planning. UBS Vila Três Marias was the most affected, suggesting serious issues or gaps in the initial construction. Infiltrations and excessive deformations were the main causes of additional costs, emphasizing the importance of careful planning and budgeting in public infrastructure to avoid high repair costs.
Keywords: Pathological manifestations; Financial impact; Repair costs; Public management